Revivification of Legends and Religious Tourism Kiai Sepuh in Community Life and Primary School Environment - Tristan Rokhmawan; Muhammad Muqoffan; Reviandy Azhar Ramdhani; Badriyatul Munawaroh; Syaikhu Affandi Khusyairi; Zahirotun Nafisa (Bulletin of Community Engagement, 2024)
The people of Gentong Village, the manager of the Kiai Sepuh tomb, and SDN Gentong Pasuruan City are faced with serious challenges in preserving valuable local cultural heritage. Modernization and globalization have brought significant changes in daily life, shifting traditional cultural values that were once highly respected. As a result, the legend of Kiai Sepuh, which used to be a source of pride and identity of the community, began to be forgotten, especially among the younger generation. This service activity has two main objectives, the first goal is to analyze the urgency of reviving the legend of Kiai Sepuh. The second goal is to carry out revival to explore the potential assets of the legend of Kiai Sepuh and increase public awareness and involvement through the Storytelling Festival. This revival aims to document and enrich the narrative of the legend of Kiai Sepuh, as well as make it an interesting and relevant socialization material. This service activity is carried out using two main methods: Asset Based Community Development (ABCD) and Community-Based Participatory Research (CBPR). The combination of story digging and activities such as oral storytelling competitions is very important in cultural revival efforts. Story digging ensures that important narratives are well documented and understood, while oral storytelling competitions allow the community to be actively involved in the preservation and dissemination of these stories. These two approaches work together to preserve and strengthen cultural heritage in modern society. Activities such as storytelling festivals and oral storytelling competitions have not only succeeded in reviving oral traditions, but also strengthened the cultural identity of the community and increased the potential for religious tourism in the area. The results of the study show that this revival effort is not only important to preserve cultural heritage, but also provides economic benefits to the local community